PENDEKATAN SAINTIFIK MENGGUNAKAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN KEMAMPUAN MENULIS TEKS ULASAN FILM - Rejeki Situmorang, Rolah Sri; Sulissusiawan, Ahadi; Syam, Christanto (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractÂ This research is motivated by the low score of students 'achievement caused by the lack of interest and the students' ability in expressing ideas in written form. In classroom teaching practice, researchers are more active than students. Classes tend to be passive, information tends to be from teacher to student. The focus of this research is to improve the ability to produce review text about the film using a scientific approach with audio-visual media. This research uses a descriptive method. The form of research is classroom action research which is carried out in three cycles. This research applied to students of class XI MIPA 2 SMA Gembala Baik Pontianak as many as 41 students. Instrument used is observation sheet and test of learning result for observation of student and teacher activity.The results of the discussion of data obtained, it appears that the increase in the value of writing skill skills on the film about the film on students starting from prasiklus s.d. cycle III. The overall percentage of mastery increases from 39% to 44% in cycle I, again in cycle II to 70%, and cycle III increases to 90%. At the end of the cycle there are 4 unfinished students based on the KKM score. Keywords: producing, review movie text, scientific